State planning organization and technocracy :|a review of planning documents of 1960-1980 period - Selim, Semih Aras. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2019., 2019)
In 1960 State Planning Organization was established to plan Turkey’s road to development. Comprehensive five-year developmental plans that covered social and cultural as well as economic aspects were prepared by a small number of young planners. For their lack of previous civil service experience, and their basis of hiring being technical education, these planners were usually called technocrats of Turkey. Although there has been voluminous work on DPT, especially by the former planners themselves, the institution’s effectiveness in development, its power vis-à-vis the politicians, and the reasons for Turkey’s failed attempt at being a developed country has been the focus. By looking at the planning documents that received less public attention and therefore contained relatively independent analyses, I seek to understand what planning tried to do rather than was it able to do it. The focus in analysis is how Turkey’s problems were identified and in what manner solutions were offered. To do so, specialization theses written by planners and special expertise commission reports prepared for five-year plans by non-DPT personnel are reviewed. A comparison between two groups involved in the planning process shows that DPT planners not always had a technocratic approach, and that a technocratic mentality was also observed in non-DPT personnel.
Keywords: Central planning -- Turkey.